MLVA Genotyping Characteristics of Human Brucella melitensis Isolated from Ulanqab of Inner Mongolia, China - Liu, Zhi-Guo; Di, Dong-Dong; Wang, Miao; Liu, Ri-Hong; Zhao, Hong-Yan; Piao, Dong-Ri; Tian, Guo-Zhong; Fan, Wei-Xing; Jiang, Hai; Cui, Bu-Yun; Xia, Xian-Zhu (Frontiers in Microbiology, 2017)
Brucellosis is a serious public health problem in Ulanqab, which is a region located in the middle of the Inner Mongolia Autonomous Region adjacent to Shanxi and Hebei provinces. The disease is prevalent in both the latter provinces and Ulanqab with the highest prevalence of brucellosis occurring in Inner Mongolia. The MLVA-16 scheme is a genotyping tool for assessing genetic diversity and relationships among isolates. Moreover, this genotyping tool can also be applied to epidemiological trace-back investigations. This study reports the occurrence of at least two B. melitensis biovars (1 and 3) in Ulanqab, encompassing 22 and 94 isolates, respectively. B. melitensis biovar 3 was the predominant biovar in the area examined. Panel 1 (MLVA-8) identified three genotypes (42, 63 and 114), with genotype 42 (n = 101) representing 87% of the tested strains. MLVA-11 identified eight genotypes (116, 111, 297, 291, and 342-345) from 116 of the analyzed isolates. All of these isolates were identified as belonging to the East Mediterranean group. Genotype 116 (n = 94) was the predominant genotype and represented 81% of the isolates. The isolates pertaining to this genotype were distributed throughout most of Ulanqab and neighboring regions. The MLVA-16 scheme showed the presence of 69 genotypes, with 46 genotypes being represented by single isolates. This analysis revealed that Ulanqab brucellosis cases had epidemiologically unrelated and sporadic characteristics. The remaining 23 genotypes were shared (between a total of 70 isolates) with each genotype being represented by two to eight isolates. These data indicate that these cases were epidemiologically related. MLVA genotyping confirmed the occurrence of a multipoint outbreak epidemic and intrafamilial brucellosis. Extensive genotype-sharing events were observed among isolates from different regions of Ulanqab and from other provinces of China. These findings suggest either a lack of control of animal movement between different regions or the circulation of contaminated animal products in the market. Our study is the first comprehensive genotyping and genetic analysis of B. melitensis in Ulanqab. We believe that this study will help to improve the effectiveness of brucellosis control programs.